Partners and ex-partners in dreams: an online survey - Schredl, Michael; Echevarria, Naiara Cadiñanos; Macary, Louise Saint; Weiss, Alexandra Francesca (International journal of dream research, 2020)
Social interactions, especially with the romantic partner, are a very important part of waking life and - in line with the continuity hypothesis of dreaming - also play an important role in dreams. In total, 1695 persons (960 women, 735 men; mean age: 53.84 ± 13.99 yrs.) completed an online survey that included questions about estimating retrospectively the frequency of partner and ex-partner(s) dreams and questions about their relationship status. These estimates indicate that partner dreams are not only common in persons with stable partnership (24%) but also in singles (16%). Partnership quality was the strongest predictor of the emotional tone of partner dreams. Ex-partner dreams were less positive than partner dreams and quite frequent - even years after separation. The next step would be to collect partner and ex-partner dream reports and study the interaction between partnership and partner dreams in a longitudinal design.